A Graphene‐Based Filament Transistor with Sub‐10 mVdec−1 Subthreshold Swing. (13th March 2018) - Tian, He; Wang, Xuefeng; Zhao, Haiming; Mi, Wentian; Yang, Yi; Chiu, Po‐Wen; Ren, Tian‐Ling
Abstract: There is a growing trend of developing steep slope transistors with subthreshold swing (SS) below 60 mV dec −1 . At present, there are mainly three kinds of steep slope transistors: tunneling transistor, negative capacitance transistor, and nano‐electromechanical relay. Here, a new kind of steep slope transistor named "filament transistor" is proposed with SS down to sub‐10 mV dec −1 . Due to the gate E‐filed can penetrate through the graphene, the gate can effectively control the filament formation/rupture inside the 5 nm AlO x with very steep slope. In reverse sweep, the gate can induce the filament formation with SS down to 4.6 mV dec −1 . In forward sweep, the gate can break the filament with SS down to 12.2 mV dec −1 . Taking the advantages of nanofilament, the filament transistor holds a great potential to scaling down to 5 nm without performance changing. Abstract : A new steep‐slope transistor named "filament transistor" is proposed with subthreshold swing (SS) down to sub‐10 mV dec −1 . The transistor operation mechanism is fundamentally different from conventional steep‐slope transistors (such as tunneling transistor and negative‐capacitance transistor). Taking advantages of nanofilament, the filament transistor holds a great potential to scaling down to 5 nm without performance changing.